Relative domain modelling based on ships group situation in restricted waters. (31st January 2022) - Wang, Xiaoyuan; Sun, Yifei; Wang, Gang; Wang, Quanzheng; He, Guowen
The ship domain is the area around the ship that should not be entered by other ships. In existing research methods, complex environmental factors or ship factors were not fully considered, which has led to the result that the dynamic change of the whole navigation environment could not be effectively or comprehensively reflected. In this paper, based on analysis of complexity of ships group situation in restricted waters, a relative domain model was established to adapt to current navigation environment. Influence of interfering ships and quay wall on the target ship was considered, and navigation dynamics of the target ship and interfering ships were both analysed. The model was verified through the combination of real ship and simulation experiments, and the results show that the model can accurately reflect the degree of navigation hazard of ships in restricted waters, and it can provide effective reference basis for collision avoidance of unmanned ships.